2021
DOI: 10.1111/jcms.13182
|View full text |Cite
|
Sign up to set email alerts
|

Ego versus Alter: Internal and External Perceptions of the EU's Role in Global Environmental Negotiations

Abstract: This paper compares how European and non‐European participants in international environmental negotiations perceive the EU's role in such negotiations. Three dimensions of the EU's role (environmental ambition, diplomatic activity and influence) are assessed in three UN‐wide environmental forums (the Basel, Rotterdam and Stockholm Conventions on chemicals, the Convention on Biological Diversity, and the United Nations Environment Assembly). The paper presents original data collected through an online survey wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 43 publications
0
0
1
Order By: Relevance
“…We did not find significant differences based on the origin of survey participants. In contrast to Charles Parker and Christer Karlsson (2018), who found that countries and regional groups are more often recognised as leaders by negotiators from the country or regional group they belong to, we do not find this pattern in our data (Delreux and Ohler 2021). In other words, our data do not show a pattern in which countries or regional groups are assessed as more ambitious, active or influential by delegates from that region than by delegates from other regions of the world.…”
Section: Role Perceptions Of Countries and Regional Groupscontrasting
confidence: 99%
“…We did not find significant differences based on the origin of survey participants. In contrast to Charles Parker and Christer Karlsson (2018), who found that countries and regional groups are more often recognised as leaders by negotiators from the country or regional group they belong to, we do not find this pattern in our data (Delreux and Ohler 2021). In other words, our data do not show a pattern in which countries or regional groups are assessed as more ambitious, active or influential by delegates from that region than by delegates from other regions of the world.…”
Section: Role Perceptions Of Countries and Regional Groupscontrasting
confidence: 99%